(3MGTjI Ydi TQM QSGdI GdGSJYGQGJ dYUGe GdOjfs - (3GdSjhGSj, ESeGYjd Hf SfGf, J(B1047(3g`s ((3YHO Gddg Hf HTjQ GdHhSfhjs)
(3ChdgG (B:s
(3GdMeO ddg Pj GdYXeI hGdSdWGfhHYO ajbhdESeGYjd Hf GdMGL SfGf GdSjhGSjCf JaSjQ GdbQBf GdYXjedG jYQa dHgEdG HeYQaI Yde GdeYGfj hGdHjGf hCfYUGe GdOjfbO TQM GdQSGdI GdJj YedgG aj JMbjb GdGSJYGQGJ CHh GdbGSe GdSeQbfOjs
(3BNQgG (B:s
(3bhdg(B: (3dCfg dG GdJHGS Hjf GdbQjfI hGdJQTjM aj GdeUQMI dCf GdbQjfI eeG jdGFe GdeTHg hGdJQTjM eeG jdGFe GdeTHg Hgs
(3fSNI efbhdI ef fSNI GdeDda GdeDQNI SfI (B1022(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 314s
(3eYLe GdeDdajf(B: 1 / 365s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdHdGZIs